Behavioral pattern analysis of the Zika virus disease: its prevention and solution / Mohd Rahimie Md Noor ... [et al.] - Md Noor, Mohd Rahimie; Mohd Nor, Wan Nur Aliaa; Ab Kadir, Liyana Qadirah; Syed Adnan, Sharifah Athirah; Mohd Yasin, Ahmad Bukhari; Abdul Malek, Mohd Azry (Universiti Teknologi MARA Cawangan Pulau Pinang, 2018)
This paper considers a non-linear ordinary differential equation model for the risk of microcephaly induced by Zika Virus (ZIKV). A model of mathematical dynamic system is required to develop a non-linear equation based on ZIKV. This research focuses on a group of pregnant women in Armedia (Quindio), Columbia. By solving the non-linear algebraic system, the equilibrium points for each possible cause that induced microcephaly can thus be obtained. The Jacobian method was then used to calculate the eigenvalues for each equilibrium point to estimate the local stability. Following this, the local stability analysis will be used to show the behavior of each equilibrium point acquired. Finally, the results were interpreted and a conclusion was made.